2019
DOI: 10.1038/s41598-019-50419-2
|View full text |Cite
|
Sign up to set email alerts
|

PKN1 kinase-negative knock-in mice develop splenomegaly and leukopenia at advanced age without obvious autoimmune-like phenotypes

Abstract: Protein kinase N1 (PKN1) knockout (KO) mice spontaneously form germinal centers (GCs) and develop an autoimmune-like disease with age. Here, we investigated the function of PKN1 kinase activity in vivo using aged mice deficient in kinase activity resulting from the introduction of a point mutation (T778A) in the activation loop of the enzyme. PKN1[T778A] mice reached adulthood without external abnormalities; however, the average spleen size and weight of aged PKN1[T778A] mice increased significantly compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 81 publications
1
4
0
Order By: Relevance
“…expression is particularly high in lymphoid tissues where it is associated with leukocyte development and their migration (Mashud et al, 2017;Siddique et al, 2019). Our work confirms these previous observations showing that PKN1 is strongly expressed in the monocyte cell line U937 and is nominally expressed in the epithelial cells tested (Figure 1a).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…expression is particularly high in lymphoid tissues where it is associated with leukocyte development and their migration (Mashud et al, 2017;Siddique et al, 2019). Our work confirms these previous observations showing that PKN1 is strongly expressed in the monocyte cell line U937 and is nominally expressed in the epithelial cells tested (Figure 1a).…”
Section: Discussionsupporting
confidence: 91%
“…PKN1 expression varies across mammalian in vitro cell lines and is largely tissue‐type specific (Cell atlas—PKN1—The Human Protein Atlas, n.d.; Lachmann et al., 2011; Thul et al., 2017). PKN1 expression is particularly high in lymphoid tissues where it is associated with leukocyte development and their migration (Mashud et al., 2017; Siddique et al., 2019). Our work confirms these previous observations showing that PKN1 is strongly expressed in the monocyte cell line U937 and is nominally expressed in the epithelial cells tested (Figure 1a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, optimized antibodies have been developed in preclinical models against different forms of mono-, oligomeric, fibrils, and aggregated forms to target different stages in α-synuclein related pathophysiology (Wang et al 2019 ). Moreover, the recent development of the SNCA gene by antisense-oligonucleotides (ASOs; short-chain, synthetic, single-stranded oligonucleotides that bind to the complementary mRNA and modify/hinder their respective translation) has already been proven useful in in-vitro, rodent, and primate models (Uehara et al 2019 ; Alarcón-Arís et al 2018 ; Choong and Mochizuki 2017 ).…”
Section: Main Bodymentioning
confidence: 99%
“…PRK1 has been implicated in lymphocyte trafficking by studies with a PRK1 kinase-inactive knock-in mouse [ 99 ], whose lymphocytes displayed reduced migration from secondary lymphoid organs to the blood and lymph. The same mouse model indicated that PRK1 also regulates trafficking of all leukocytes [ 100 ].…”
Section: Physiological Rolesmentioning
confidence: 99%